The Functional Role of Olfactory Bulb Granule Cell Subtypes Derived From Embryonic and Postnatal Neurogenesis - Takahashi, Hiroo; Yoshihara, Seiichi; Tsuboi, Akio (Frontiers in Molecular Neuroscience, 2018)
It has been shown in a variety of mammalian species that sensory experience can regulate the development of various structures, including the retina, cortex, hippocampus and olfactory bulb. In the mammalian olfactory bulb, the development of dendrites in excitatory projection neurons, such as mitral and tufted cells, is well known to be dependent on odor experience. Odor experience is also involved in the development of another olfactory bulb population, a subset of inhibitory interneurons that are generated in the ventricular-subventricular zone throughout life and differentiate into granule cells and periglomerular cells. However, the roles that each type of interneuron plays in the control of olfactory behaviors are incompletely understood. We recently found that among the various types of olfactory bulb interneurons, a subtype of granule cells expressing the oncofetal trophoblast glycoprotein 5T4 gene is required for odor detection and discrimination behaviors. Our results suggest that embryonic-born olfactory bulb interneurons, including 5T4-positive granule cells, play a crucial role in fundamental olfactory responses such as simple odor detection and discrimination behaviors. By contrast, postnatal- and adult-born olfactory bulb interneurons are important in the learning of more complicated olfactory behaviors. Here, we highlight the subtypes of olfactory bulb granule cells, and discuss their roles in olfactory processing and behavior, with a particular focus on the relative contributions of embryonically- and postnatally-generated subsets of granule cells in rodents.